PENGARUH WORK FAMILY CONFLICT DAN JOB SATISFACTION TERHADAP TURNOVER INTENTION KARYAWAN DI HOTEL MANDAPA, A RITZ-CARLTON RESERVE UBUD - DEWI, NI LUH GEDE ANGGRENI PUSPITA; WIDIANTARA, I MADE; WIJAYATI, NI LUH MADE (GANEC SWARA, 2024)
The hospitality industry is part of the service industry whose business activities are strongly dependent on employees so the level of concern about employee turnover is very high. Employee turnover is not desired by the company because it bring more disadvantages to the business. One of the large companies in the hospitality industry, Ritz-Carlton, experiences a high level of employee turnover. The rate of employee turnover can be known from employee turnover intention. The purpose of this study is to determine the effect of work family conflict dan job satisfaction on employee turnover intention at Hotel Mandapa, a Ritz-Carlton Reserve Ubud. This type of research is a quantitative study, with data collected from 103 employee through questionaries. The data analysis technique using multiple linier regression analysis with SPSS version 25. The results of analysis obtained that the work family conflict has a positive and significant effect on turnover intention. The job satisfaction has a negative and significant effect on turnover intention. Work family conflict and job satisfaction simultaneously have a positive and significant effect on turnover intention